Creencias acerca del aprendizaje de una lengua extranjera en un programa de formación inicial de profesores de inglés en Chile - Ormeño, Verónica; Rosas, Minerva (Colombian Applied Linguistics Journal, 2015)
This quantitative and qualitative case study aims at identifying and categorizing university students’ and academics’ beliefs about learning a foreign language; at comparing the differences in beliefs held by these students from three different semesters and academics from a Chilean university teacher education program about how to learn an L2; and at establishing whether there is any relationship among the subjects’ tolerance of ambiguity levels, their predominating types of beliefs and their academic level. The quantitative instruments included the BALLI by Horwitz (1987) and the Second Language Tolerance of Ambiguity Scale by Ely (1989). Based on experts’ judgments, the BALLI beliefs were classified into three categories: facilitating beliefs of L2 learning, potentially detrimental beliefs of L2 learning, and neutral beliefs. A focus group was conducted with a student sample to elucidate the origin of their beliefs, and content analysis was used on the qualitative data obtained. Differences among the groups were found at the level of specific beliefs but not at the level of the BALLI dimensions. Most subjects were found to hold medium levels of Tolerance of Ambiguity, with no clear relation between these and the type of beliefs nor the students’ academic level.